Aquatic Plant and Fish Assosiation in the Parit Belanda River, Meranti Pandak Village, Rumbai Pesisir District, Pekanbaru Regency, Riau Province - Fariza Ulfa; Efawani '; Windarti ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
There are many types of aquatic plant and fish in the Parit Belanda River, but there is no information on the assosiation of aquatic plant and fish in the river. To understand that assosiation, a research has been conducted in February – March 2016. Sampling were conducted once /week for a month period. Poecilia reticulata, Trichopsis vittata, Aplocheilus pancha and Oreochromis niloticus were found around the community of Paspalum sp. Around the Eichhornia crassipes community, there were T. vittata, Rasbora einthovenii, P. reticulata, Trichogaster trichopterus, and Esomus metallicus present. While T. trichopterus, R. einthovenii, E. metallicus, Oxygaster anomarula, P. reticulata, and T. vittata were found around the Ipomoea aquatica community. There is similarity in fish species present around different aquatic plants. Based on data obtained, it can be concluded that there is no specific association between aquatic plant and fish species in the Parit Belanda River.Keywords: Aquatic plant, fish, assosiation, Parit Belanda River